AgNO3 - a potential regulator of ethylene activity and plant growth modulator - Kumar, Vinod; Parvatam, Giridhar; Ravishankar, Gokare Aswathanarayana (Electronic Journal of Biotechnology, 2009)
The aim of this review is to critically analyze the role of silver nitrate (AgNO3) in modulating plant growth and development. In recent years, basic studies on ethylene regulation opened new vistas for applied research in the area of micro-propagation, somatic embryogenesis, in vitro flowering, growth promotion, fruit ripening, and sex expression. Silver nitrate has proved to be a very potent inhibitor of ethylene action and is widely used in plant tissue culture. Few properties of silver nitrate such as easy availability, solubility in water, specificity and stability make it very useful for various applications in exploiting plant growth regulation and morphogenesis in vivo and in vitro. Silver ion mediated responses seem to be involved in polyamines, ethylene- and calcium- mediated pathways, and play a crucial role in regulating physiological process including morphogenesis. The molecular basis for regulation of morphogenesis under the influence of silver nitrate is completely lacking. This review compiles published reports of silver nitrate-mediated in vitro and in vivo studies and focuses on fundamental and applied aspects of plant growth modulation under the influence of silver nitrate.